Answer:
(0, -1)
Step-by-step explanation:
There are multiple ways of solving this however- since both equations are already in Y-Intercept form, we will use the "Equal Values Method"
First, since both equations are equal to Y, we can set them equal to each other and solve for X
[tex] \frac{3 }{4} x - 1 = \frac{4}{3} x - 1[/tex]
To start, you must eliminate the fraction using a "fraction buster" multiply EVERYTHING by 4 then simplify.
[tex]3x - 4 = 5 \frac{1}{3}x - 4[/tex]
Since we still have a fraction, we shall do it one more time. This time we multiply by 3
[tex]9x - 12 = 6 x - 12[/tex]
Now, solve how you normally would.
9x = 6x
-6x
3x = 0
X = 0
Now, since we know what X would equal in the solution, we are able to plug in X as 0 in one of our equations. We can choose the first one!
[tex]y = \frac{3}{4} (0) - 1[/tex]
Now solve which would lead to y = -1
You have your solution as
(X,Y)
(0,-1)
Hope this helps!